أثر ممارسة أخلاقيات العمل على مستوى فاعلية اتخاذ القرار الإداري في مراكز شركات التأمين الأردنية من وجهة نظر الإدارة الإشرافية - الزعبي, عروة; الشياب, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف على أثر ممارسة أخلاقيات العمل على مستوى فاعلية اتخاذ القرار الإداري لدى العاملين في المواقع الإدارية الإشرافية ممثلة بالإدارتين العليا والوسطى في مراكز شركات التأمين الأردنية. تم استخدام المنهج الوصفي التحليلي، ووزعت (466) استبانه على أفراد العينة الذين يشغلون المواقع الإدارية الإشرافية في مراكز شركات التأمين الأردنية، حيث أن مجتمع الدراسة هو ذاته عينة الدراسة، وقد توصلت الدراسة إلى وجود مستوى عالٍ لممارسة أخلاقيات العمل بأبعاده ( إدارة الموارد البشرية، التسويق، الإدارة المالية والمحاسبية ) لدى العاملين في المواقع الإدارية الإشرافية في مراكز شركات التأمين الأردنية، ومستوى متوسط لممارسة أخلاقيات العمل في بعد أخلاقيات العمل تجاه المجتمع، ووجود مستوى متوسط لفاعلية اتخاذ القرار الإداري لدى العاملين في المواقع الإدارية الإشرافية بأبعاده المختلفة، كما تبين وجود أثر هام ذو دلالة إحصائية لمستوى ممارسة أخلاقيات العمل على مستوى فاعلية اتخاذ القرار الإداري. وقد أوصت الدراسة بضرورة اهتمام شركات التأمين بشكل أكبر بتعزيز الممارسات الأخلاقية تجاه المجتمع بما يعود بالنفع والفائدة عليها وعلى المجتمع بآنٍ واحد ، وتشجيع الموظفين على إبداء آرائهم من أجل تطوير العمل وتنفيذ القرارات بالشكل الفعال. This study aimed to identify the practice impact of work ethics on effectiveness level of the administrative decision-making at occupants of supervisory administrative positions represented by upper and middle managements at the centers of Jordanian insurance companies. It has been used a descriptive analytical method, where (466) questionnaires were distributed among respondents who occupy supervisory administrative positions at the centers of Jordanian insurance companies, as the population of the study is the same as the study sample. The study found a high practice level of work ethics in its dimensions (human resources management, marketing, financial and accounting management) among employees at supervisory administrative positions at the centers of Jordanian insurance companies, and a medium level of practicing work ethics in the dimension toward society, existence of a medium level of administrative decision-making effectiveness among employees at supervisory administrative , the study also showed a statistically significant impact of the practice level of work ethics on effectiveness level of the administrative decision-making. The study recommended urging insurance companies to promote ethical practices towards society for the benefit and interest of them and society, and encouraging employees to express their opinions in order to develop the work and the implementation of decisions effectively .